Using a Full Spectral Raytracer for Calculating Light Microclimate in Functional-Structural Plant Modelling - Henke, Michael; Buck-Sorlin, Gerhard H. (Computing and Informatics, 2018)
Raytracers that allow the spatially explicit calculation of the fate of light beams in a 3D scene allow the consideration of shading, reflected and transmitted light in functional-structural plant models (FSPM). However, the spectrum of visible light also has an effect on cellular and growth processes. This recently created the interest to extend this modelling paradigm allowing the representation of detailed spectra instead of monochromatic or white light and to extend existing FSPM platforms accordingly. In this study a raytracer is presented which supports the full spectrum of light and which can be used to compute spectra from arbitrary light sources and their transformation at the organ level by absorption, reflection and transmission in a virtual canopy. The raytracer was implemented as an extension of the FSPM platform GroIMP.